2003
DOI: 10.1111/j.1365-2559.2003.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node reticulum cell neoplasm with progression into cytokeratin‐positive interstitial reticulum cell (CIRC) sarcoma: a case study

Abstract: We speculate that the morphological changes and p53 expression of the relapsing neoplasm might reflect tumour cell dedifferentiation, in keeping with the aggressive clinical course. The intense p53 expression suggests that this oncoprotein might also play a role in reticulum cell tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…CIRCs have been identified as the cell type of origin of a special group of tumors, usually referred to as CIRC tumors or CIRC sarcomas. Following their first description by Gould et al (1990), a series of publications have confirmed the existence of this tumor group and have added further valuable biological and clinical observations (e.g., Gould et al 1995;Chan et al 2000;Lucioni et al 2003;Schuerfeld et al 2003;Dong et al 2008). In general, cytokeratin positivity, especially for keratins 8 and 18, and desmoplakin-negative reactions are at present the most valuable immunohistochemical characteristics of these genuine lymph node sarcomas, which include some rather aggressive forms.…”
Section: Circ Tumorsmentioning
confidence: 98%
“…CIRCs have been identified as the cell type of origin of a special group of tumors, usually referred to as CIRC tumors or CIRC sarcomas. Following their first description by Gould et al (1990), a series of publications have confirmed the existence of this tumor group and have added further valuable biological and clinical observations (e.g., Gould et al 1995;Chan et al 2000;Lucioni et al 2003;Schuerfeld et al 2003;Dong et al 2008). In general, cytokeratin positivity, especially for keratins 8 and 18, and desmoplakin-negative reactions are at present the most valuable immunohistochemical characteristics of these genuine lymph node sarcomas, which include some rather aggressive forms.…”
Section: Circ Tumorsmentioning
confidence: 98%
“…Further negativity for both desmin and anaplastic lymphoma kinase (ALK) is helpful to exclude an inflammatory myofibroblastic tumor [6,8,9]. Most of these immunohistochemical features support the diagnosis of CIRCT in the present tumor with epithelioid cell morphology.…”
Section: Discussionmentioning
confidence: 52%
“…5 Immunostaining of neoplastic cells with cytokeratin AE1/AE3 (×400) Fig. 6 Immunostaining of neoplastic cells with Ki67 (×400) dendritic cells (FDC and IDC sarcomas), myofibroblasts, and malignant mesenchymal tumors (i.e., various sarcomas, sarcomatoid variant of anaplastic large-cell lymphoma and malignant melanoma) as they have no characteristic clinical symptoms or histological features [2,6]. The lack of awareness of these tumors or their expression of cytokeratin and epithelioid morphology lead to a misdiagnosis of metastatic carcinoma, particularly when they are of nodal origin in patients with known carcinoma [2,4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported in 2003, one 70-year-old female patient with FBRC of an enlarged submandibular lymph node underwent surgical excision alone and five months later the tumour relapsed with progression into an interstitial reticulum cell sarcoma (CIRC) with fatal outcome (23). Although lymph node accessory cells were recognized nearly 20 years ago (3,24), clinicopathological features of neoplasms derived from fibroblastic reticular cells have only been convincingly described in five cases (1,2,22).…”
mentioning
confidence: 99%